The Effectiveness Of An Interactive Courseware Using Three Different Strategies In The Learning Of Matrices [LB2372.M43 T314 2006 f rb]. - Teoh, Sian Hoon (2006)

(untitled)
Penyelidikan ini mengkaji kesan kognitif yang diukur dari skor perolehan dan juga masa melakukan kerja melalui tiga strategi pembelajaran, iaitu ‘Computerassisted Cooperative Learning‘ (CCL), ‘Computer-assisted Mastery Learning’ (CML) dan ‘Computer-assisted Cooperative Mastery Learning’ (CCML).